DINAMIKA INTERAKSI SOSIAL DI KELAS IMPLIKASI TERHADAP PRESTASI SISWA DALAM PSIKOLOGI PENDIDIKAN - Tarsono; Hilmi Taftajani; Muhamad Ihsan; Khotibul Umam; Mochammad Ilham Rohwandi; Muhammad Haikal Zaki (STAI Pelabuhan Ratu, 2024)
Social interaction in the classroom has a significant impact on student learning achievement. From an educational psychology perspective, the dynamics of social interactions between students and teachers and their relationship with academic achievement are the main focus in formulating effective educational strategies. This article aims to explore various aspects of the dynamics of social interaction in the classroom and analyze their implications for junior high school students' learning achievement in the context of Islamic education. This research is included in library research. This literature study research is research where the data source comes from the literature which is then collected into one. Social interactions are forms that are visible when individuals or groups of people present relationships with each other, especially by prioritizing groups and social layers as the main elements of social structure. Learning achievement is the level of success of students in studying material at school, in the form of scores obtained from exams related to several materials. A conducive classroom climate encourages students to be passionate about learning and study good subject matter. Judging from the explanation above, it is very clear that social interaction in the classroom can influence learning achievement so special attention is needed to increase knowledge, especially Educational Psychology.